Water pollution in India: Law and enforcement - "Desai, Bharat" (New Delhi, 1990)
The present study strives to examine as to how water pollution is dealt with in International Law as well as some of the existing international eco standards which can be assimilated as part of de lege lata (accepted body of binding norms). These legal standards provide substantive principles and may find applicability to different problems of environmental harm, including that caused by water pollution.
Keywords: Pollution